Проблемы и перспективы развития рынка туристических услуг в Крыму - Мамедов, Л.А. (Культура народов Причерноморья, 2014)
Рынок туристско-рекреационных услуг в Крыму является одним из основных и перспективных направлений развития отечественной экономики. В статье рассматриваются проблемы и перспективы развития рынка туристических услуг в Крыму. Приводятся результаты исследований, направленные на выявление назревших и постоянно возникающих новых проблем в организации и проведении очередного курортного сезона. В данной работе также рассматриваются ресурсы и факторы, влияющие на развитие рынка туристско-рекреационных услуг в Крыму. Такие виды туризма, как экологический, приключенческий и сельский, рассматриваются в качестве конкурентоспособной альтернативы другим видам деятельности туристической отрасли. Ринок туристсько-рекреаційних послуг в Криму є одним з основних та перспективних напрямків розвитку вітчизняної економіки. У статті розглядаються проблеми та перспективи розвитку ринку туристичних послуг у Криму. Наводяться результати досліджень, спрямовані на виявлення назрілих і постійно виникаючих нових проблем в організації та проведенні чергового курортного сезону. У поданій роботі також розглядаються ресурси і фактори, що впливають на розвиток ринку туристично-рекреаційних послуг у Криму. Такі види туризму, як екологічний, пригодницький і сільський, розглядаються в якості конкурентоспроможної альтернативи іншим видам діяльності туристичної галузі. The market of tourist services in the Crimea is the main and long-range tendencies in the development of the domestic economy. The article considers the problems and prospects of development of the market of tourist services in the Crimea. The author gives the results of studies that identify the main problems of the tourist and recreational complex in the region. This work discusses the resources and factors which are affecting the development of the market of tourism and recreational services in the Crimea. Eco-tourism, adventure tourism and rural tourism are seen as competitive alternative to other types of the tourism. In the future the unification of the market researches will allow to conduct the monitoring of the market of the tourism and recreational services of the Crimea to develop a balanced and reasonable tourist and recreational policy, decision-making in the field of investment, innovation management, taxation, employment, transport and other, not only at the level of the individual resort areas Crimea, but the whole of the peninsula as a whole. There are a number of unresolved issues and recommendations for the economic development of the peninsula, such as the state approach to the management and control of the hotel enterprises, establishment of effective communication between local government and the tourist industry, spatial distribution of enterprises of hotel complexes, organization of a statistical registry of hotel enterprises of different ownership forms, standardization and certification sanatorium and hotel businesses for tourists, investment management and innovative hotel businesses, creation and implementation of programs for the development of quality infrastructure and tourist services;